Gut microbiota richness promotes its stability upon increased dietary fibre intake in healthy adults. (3rd September 2015) - Tap, Julien; Furet, Jean‐Pierre; Bensaada, Martine; Philippe, Catherine; Roth, Hubert; Rabot, Sylvie; Lakhdari, Omar; Lombard, Vincent; Henrissat, Bernard; Corthier, Gérard; Fontaine, Eric; Doré, Joël; et al.
Summary: Gut microbiota richness and stability are important parameters in host–microbe symbiosis. Diet modification, notably using dietary fibres, might be a way to restore a high richness and stability in the gut microbiota. In this work, during a 6‐week nutritional trial, 19 healthy adults consumed a basal diet supplemented with 10 or 40 g dietary fibre per day for 5 days, followed by 15‐day washout periods. Fecal samples were analysed by a combination of 16S rRNA gene pyrosequencing, intestinal cell genotoxicity assay, metatranscriptomics sequencing approach and short‐chain fatty analysis. This short‐term change in the dietary fibre level did not have the same impact for all individuals but remained significant within each individual gut microbiota at genus level. Higher microbiota richness was associated with higher microbiota stability upon increased dietary fibre intake. Increasing fibre modulated the expression of numerous microbiota metabolic pathways such as glycan metabolism, with genes encoding carbohydrate‐active enzymes active on fibre or host glycans. High microbial richness was also associated with high proportions of Prevotella and Coprococcus species and high levels of caproate and valerate. This study provides new insights on the role of gut microbial richness in healthy adults upon dietary changes and host microbes' interaction